2004
DOI: 10.1023/b:trag.0000026072.01351.10
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Mice Over-expressing Endothelin-1 in Testis Transactivated by a Cre/loxP System Showed Decreased Testicular Capillary Blood Flow

Abstract: It is generally believed that too high or low levels of endothelin-1 (ET-1), a strong vasoconstrictor, may be detrimental to animals. Therefore, in order to understand the in vivo function of ET-1, we used a conditional transgenic approach, Cre/loxP recombination system, to generate transgenic mice that over-express ET-1 in a tissue-specific manner. In such a strategy a single transgenic mouse line, ELSE, was initially generated where a general promoter, human elongation factor 1alpha (hEF1alpha) promoter, was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…This has become the basic assumption since the Cre-loxP technology was first applied to conditionally express transgenes in mice in 1992 [1], [2]. In recent years, the use of loxP-containing transgenes in transgenic mice has increased but the possibility of unintended effects of this approach has not been taken into consideration [5], [7], [8], [9], [10], [11], [12], [13], [14], [37], [38], [39], [40], [41]. Our data demonstrate that, contrary to the widely held assumption that transgenes are integrated into the genome in a head-to-tail tandem array [5], [7], [8], [9], [10], [11], [12], [13], [14], [28], [29], [30], [37], [38], [39], [40], [41], inverted transgene integration is common when multiple copies of the transgene are integrated into the genome.…”
Section: Discussionmentioning
confidence: 99%
“…This has become the basic assumption since the Cre-loxP technology was first applied to conditionally express transgenes in mice in 1992 [1], [2]. In recent years, the use of loxP-containing transgenes in transgenic mice has increased but the possibility of unintended effects of this approach has not been taken into consideration [5], [7], [8], [9], [10], [11], [12], [13], [14], [37], [38], [39], [40], [41]. Our data demonstrate that, contrary to the widely held assumption that transgenes are integrated into the genome in a head-to-tail tandem array [5], [7], [8], [9], [10], [11], [12], [13], [14], [28], [29], [30], [37], [38], [39], [40], [41], inverted transgene integration is common when multiple copies of the transgene are integrated into the genome.…”
Section: Discussionmentioning
confidence: 99%
“…Although these data demonstrated that ET-1 is involved in the regulation of human fertility, no evidence is currently available suggesting a physiological direct relationship between ET-1 and parameters indicative of sperm functions [190]. A genetically modified mouse model with ET-1 overexpression had reduced testicular blood flow, but neither increased inflammatory status, nor impaired cell proliferation [184]. Hypothetically, ET-1 dysfunction could impair sperm progression through the genital tract, negatively impacting the viability of gametes in the ejaculate.…”
Section: Role Of Endothelin-1 and Sperm Functionmentioning
confidence: 91%
“…In the male genital tract, endothelin-1 (ET-1) is detectable at testicular, epididymal and prostatic levels both in human and in rat males [184,185]. Within the testis, ET receptors were mainly found in Leydig cells, in which they promote testosterone secretion [186] In Sertoli cells, ET receptors are involved in micro-tubule contractility [187].…”
Section: Role Of Endothelin-1 and Sperm Functionmentioning
confidence: 99%